Pedigree tests of transmission disequilibrium. - Abecasis,GR; Cookson,WO; Cardon,LR (Eur J Hum Genet, 2000)
High-resolution mapping is essential for the positional cloning of complex disease genes. In outbred populations, linkage disequilibrium is expected to extend for short distances and could provide a powerful fine-mapping tool. Current family-based association tests use nuclear family members to define allelic transmission and controls, but ignore other types of relatives. Here we construct a general approach for scoring allelic transmission that accommodates families of any size and uses all available genotypic information. Family data allows for the construction of an expected genotype for every non-founder, and orthogonal deviates from this expectation are a measure of allelic transmission. These allelic transmission scores can be used to extend previously described tests of linkage disequilibrium for dichotomous or quantitative traits. Some of these tests are illustrated, together with a permutation framework for estimating exact significance levels. Simulation studies are used to investigate power and error rates of the approach. As a practical application, the method is used to investigate the relationship between circulating angiotensin-1 converting enzyme (ACE) levels and polymorphisms in the ACE gene using previously published data.